Excavations at Kiriath-jearim, 2019: Preliminary Report. (2nd January 2021) - Finkelstein, Israel; Römer, Thomas; Nicolle, Christophe; Dunseth, Zachary C.; Kleiman, Assaf; Mas, Juliette; Porat, Naomi; Walzer, Naama
Abstract : In this article we report the results of the second season of excavations at Kiriath-jearim (Deir el-ʿAzar). The following topics are emphasized: layout and date of the supposed monumental Iron IIB summit compound; nature of the Iron IIC settlement; date of the Hellenistic fortification; characteristics of the Early Roman period activity. An archaeo-historical analysis follows the presentation of the new data, including updates on past interpretations.